Geotechnical and Structural Aspects of the Design of a Tailings Thickener - Clemente, J.L.M.; de la Cuadra, P.; Verdugo, A.; Canteros-Gormaz, C. (Paste 2009: Proceedings of the Twelfth International Seminar on Paste and Thickened Tailings, 2009)
A 135 m diameter tailings thickener for expansion of a copper concentrator was designed and built in the Chilean Andes. Design challenges included high seismicity, the presence of an existing fill layer containing large particles placed in thick lifts over a sloping ground surface with limited compaction control about 10 years prior to construction of the tailings thickener, and a previous history of settlement problems of two neighbouring thickeners. Solutions adopted for the new thickener included the use of piles to support the concrete central core of the new tailings thickener, transition concrete slabs to support the geomembrane lining system where it was connected to the concrete central core to prevent rupture of the liner in the event of seismic settlements, and continuous reinforced concrete elements for the perimeter concrete water collection system. The thickener has been built and successfully hydrotested.